Characterization of neuroendocrine tumors in heterozygous mutant MENX rats: a novel model of invasive medullary thyroid carcinoma. Issue 2 (February 2018) - Molatore, Sara; Kügler, Andrea; Irmler, Martin; Wiedemann, Tobias; Neff, Frauke; Feuchtinger, Annette; Beckers, Johannes; Robledo, Mercedes; Roncaroli, Federico; Pellegata, Natalia S
Abstract : Rats affected by the MENX syndrome spontaneously develop multiple neuroendocrine tumors (NETs) including adrenal, pituitary and thyroid gland neoplasms. MENX was initially reported to be inherited as a recessive trait and affected rats were found to be homozygous for the predisposing Cdkn1b mutation encoding p27. We here report that heterozygous MENX-mutant rats (p27+/mut) develop the same spectrum of NETs seen in the homozygous (p27mut/mut) animals but with slower progression. Consequently, p27+/mut rats have a significantly shorter lifespan compared with their wild-type (p27+/+) littermates. In the tumors of p27+/mut rats, the wild-type Cdkn1b allele is neither lost nor silenced, implying that p27 is haploinsufficient for tumor suppression in this model. Transcriptome profiling of rat adrenal (pheochromocytoma) and pituitary tumors having different p27 dosages revealed a tissue-specific, dose-dependent effect of p27 on gene expression. In p27+/mut rats, thyroid neoplasms progress to invasive and metastatic medullary thyroid carcinomas (MTCs) accompanied by increased calcitonin levels, as in humans. Comparison of expression signatures of late-stage vs early-stage MTCs from p27+/mut rats identified genes potentially involved in tumor aggressiveness. The expression of a subset of these genes was evaluated in human MTCs and found to be associated with aggressive RET-M918T-positive tumors. Altogether, p27 haploinsufficiency in MENX rats uncovered a novel, representative model of invasive and metastatic MTC exploitable for translational studies of this often aggressive and incurable cancer.